Case report: 18F-FDG PET confirmed pupil-sparing third nerve palsy heralding aseptic cavernous sinus embolism in patient with chest malignancy - Xiong, Jianmei; Liu, Huanbo; Li, Jianyong; Hou, Jiajia; Cui, Fang (Frontiers in Surgery, 2022)
Classical cavernous sinus embolism is a rare clinical finding, presented most commonly by complaints of headache, diplopia, visual field defects, facial pain, and progressive neurological deficits. Many patients exhibit symptoms of III, IV, and VI nerve palsies. We hereby report a rare case of aseptic cavernous sinus embolism developed in a 75-year-old male with primary lung cancer who presented with binocular diplopia due to unilateral third and sixth cranial nerve palsies with pupil-sparing. The possibility of cavernous sinus cancer embolus should be considered if the routine examination excluded metastases, infiltration, carcinomatous meningitis, or the paraneoplastic process. 18F-FDG PET imaging may provide a promising diagnostic modality for the diagnosis of cancer embolus.